2019
DOI: 10.1152/physrev.00039.2017
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells and Their Use in Human Models of Disease and Development

Abstract: The discovery of somatic cell nuclear transfer proved that somatic cells can carry the same genetic code as the zygote, and that activating parts of this code are sufficient to reprogram the cell to an early developmental state. The discovery of induced pluripotent stem cells (iPSCs) nearly half a century later provided a molecular mechanism for the reprogramming. The initial creation of iPSCs was accomplished by the ectopic expression of four specific genes (OCT4, KLF4, SOX2, and c-Myc; OSKM). iPSCs have sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
182
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(209 citation statements)
references
References 399 publications
3
182
0
3
Order By: Relevance
“…However, adult stem cells are scattered throughout tissues and their expansion is impaired or limited by their proliferative ability. To overcome these limitations, a solution is represented by induced pluripotent stem cells (iPSCs), which have been tested in many well-reviewed studies [ 110 , 111 ]. IPSCs can be produced from different cell types, but most often from fibroblasts.…”
Section: Bioprintingmentioning
confidence: 99%
“…However, adult stem cells are scattered throughout tissues and their expansion is impaired or limited by their proliferative ability. To overcome these limitations, a solution is represented by induced pluripotent stem cells (iPSCs), which have been tested in many well-reviewed studies [ 110 , 111 ]. IPSCs can be produced from different cell types, but most often from fibroblasts.…”
Section: Bioprintingmentioning
confidence: 99%
“…These induced pluripotent stem cells (iPSCs) possess almost the same features as ESCs and represent an incredibly promising source of autologous cells for transplantation purposes. Following this original discovery, numerous studies reported the ability of different somatic cell types (such as keratinocytes or blood cells) to be reprogrammed and the development of non-integrative delivery methods (such as episomal plasmids or RNA) for reprogramming (González et al, 2011;Karagiannis et al, 2019).…”
Section: Therapeutic Strategies For Photoreceptor Degenerative Diseasesmentioning
confidence: 99%
“…Yamanaka factors (Oct3/4, Sox2, Klf4, c-Myc) are highly expressed in embryonic stem (ES) cells, and their over-expression has been shown to induce pluripotency and immortalization in both mouse and human somatic cells. These factors regulate the signaling network necessary for ES cell pluripotency and, typically, human iPSCs express stem cell markers and are capable of producing differentiated cells characteristic of all three germ layers [4][5][6]. In the work described here, we employed this approach towards a slightly different goal: to immortalize and restore tumorigenic properties to human PCSC.…”
Section: Research Papermentioning
confidence: 99%